The longitudinal mediating effect of life-space mobility on the relationship between nutritional status and cognitive function in community-dwelling older stroke patients - Lei, Yixian; Bai, Haixin; Kang, Hongna; Xin, Qi; Li, Tingting; Yang, Tinghui; Li, Jianan; Meng, Lina (Frontiers in Public Health, 2025)
ObjectivesThis study aims to explore the causal relationship between nutritional status, life-space mobility (LSM), and cognitive function in community-dwelling older stroke patients, investigate the longitudinal mediating role of life-space mobility in the relationship between nutritional status and post-stroke cognitive function.MethodsA total of 284d ischemic stroke patients aged ≥60 years were recruited from the neurology inpatient department of a tertiary hospital, with follow-up assessments conducted at 3-, 6-, and 9- months post-stroke. Mini Nutrition Assessment-Short Form (MNA-SF) were used to assess nutritional status, the Life Space Assessment (LSA-C) was used to measure life-space mobility and the global cognitive function was assessed with the Mini Mental State Examination (MMSE). Linear mixed-effects model and cross-lag-panel model was applied to examine the longitudinal relations among the variables.ResultsLMM analysis revealed a significant total effect of nutritional status on post-stroke cognitive function (Estimate = 0.026, 95%CI [0.022, 0.030], p < 0.001). A significant indirect effect through LSM was identified (Estimate = 0.006, 95% CI [0.004, 0.008], p < 0.001), accounting for 24.94% of the total effect. After controlling for the longitudinal influence of LSM, the direct effect remained significant (Estimate = 0.019, 95%CI [0.015, 0.023], p < 0.001), indicating a partial mediating role of LSM. In contrast, the CLPM revealed a complete mediation effect for the T2-T3 pathway, with a significant indirect effect (β = 0.029, 95%CI [0.004, 0.061], p < 0.05) and a non-significant direct effect, providing complementary evidence for the mediating role of life-space mobility through a different analytical approach.ConclusionIn the chronic rehabilitation phase of older stroke patients, malnutrition can indirectly influence the development or exacerbation of post-stroke cognitive impairment via limited life-space mobility. This underscores the importance for early malnutrition identification and intervention and life-space mobility improvement to enhance long-term cognitive function in post-stroke care.